2023
DOI: 10.1186/s12974-023-02780-3
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytic CXCL5 hinders microglial phagocytosis of myelin debris and aggravates white matter injury in chronic cerebral ischemia

Abstract: Background Chronic cerebral ischemia induces white matter injury (WMI) contributing to cognitive decline. Both astrocytes and microglia play vital roles in the demyelination and remyelination processes, but the underlying mechanism remains unclear. This study aimed to explore the influence of the chemokine CXCL5 on WMI and cognitive decline in chronic cerebral ischemia and the underlying mechanism. Methods Bilateral carotid artery stenosis (BCAS) m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…1 ). These results are consistent with previous research [ 33 , 34 ]. Our data could not exclude the possibility that CXCR2 was also expressed in neurons following TBI.…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…1 ). These results are consistent with previous research [ 33 , 34 ]. Our data could not exclude the possibility that CXCR2 was also expressed in neurons following TBI.…”
Section: Resultssupporting
confidence: 94%
“…Under normal conditions, CXCR2 is mainly expressed in neurons [ 33 ]. Also, immunofluorescence staining demonstrated that CXCR2 was highly expressed in activated microglia of chronic ischemia-induced white matter injury [ 34 ]. Of particular noteworthy, we discovered that administration of competitive CXCR2 antagonist SB332235 resulted in the substantial decrease in CXCL1 and CXCR2 levels at 3 days post TBI.…”
Section: Discussionmentioning
confidence: 99%
“…Myelin debris preparation followed established protocols. 30 , 31 In summary, mice were humanely euthanized, and brain samples were isolated and cut into approximately 5 × 5 × 5 mm 3 sections. The solution was transferred to a 0.83 M sucrose solution.…”
Section: Methodsmentioning
confidence: 99%
“…Primary oligodendrocytes originate from the proliferation and differentiation of oligodendrocyte precursor cells (OPCs) based on previous experiments. 31 , 32 OPCs were obtained from newborn C57BL/6 pups (postnatal 0–2; P0–2). Following the removal of the meninges, cortical tissues were mechanically minced and dissociated.…”
Section: Methodsmentioning
confidence: 99%
“…A stereotaxic intracranial injection was performed following established protocols [ 19 ]. The injection site for the corpus callosum (CC) was determined based on the brain map, with coordinates of 1 mm lateral from the midline, 0.8 mm anterior from the bregma, and 2.2 mm deep from the bregma.…”
Section: Methodsmentioning
confidence: 99%